Support of Family and Friends for Postpartum Mothers of Vaginal Delivery and Sectio Caesarea - Ifada, Hanifia; Rahayuningsih, Faizah Betty (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose : This study is to compare the assistance that friends and family provide postpartum women based on caesarean section versus vaginal delivery.Method: A questionnaire-style experimental design was used in this quantitative study kind. In this study, a cross-sectional strategy was adopted. On a scale of 1 to 5, respondents were asked to rate their level of satisfaction with family assistance. The support of family and friends is the study's variable.Results: There is no discernible difference between moms who give birth naturally/vaginally and mothers who give birth by sectio caesarea/caesarean section in terms of the support from family and friends. Compared to mothers who gave birth via sectio caesarea/cesarean section, mothers who gave birth vaginally/normally received somewhat more encouragement from family and friends.Applications/Originality/Values: My research is different from earlier studies in a number of ways. One of these is when seen from a location research, which obviously has distinct features in order to produce different results. In prior investigations, the variable indicators revealed more discrepancies.